Therapeutic Plasma Concentrations of Epsilon Aminocaproic Acid and Tranexamic Acid in Horses. (1st October 2013) - Fletcher, D.J.; Brainard, B.M.; Epstein, K.; Radcliffe, R.; Divers, T.
<x xml:space="preserve">Abstract</x> Background Antifibrinolytic drugs such as epsilon aminocaproic acid (EACA) and tranexamic acid (TEA) are used to treat various bleeding disorders in horses. Although horses are hypofibrinolytic compared to humans, dosing schemes have been derived from pharmacokinetic studies targeting plasma concentrations in humans. Hypothesis/Objectives We hypothesized therapeutic plasma concentrations of antifibrinolytic drugs in horses would be significantly lower than in humans. Our objective was to use thromboleastography (TEG) and an in vitro model of hyperfibrinolysis to predict therapeutic concentrations of EACA and TEA in horses and humans. Animals Citrated plasma collected from 24 random source clinically healthy research horses. Commercial pooled human citrated plasma with normal coagulation parameters was purchased. Methods Minimum tissue plasminogen activator (tPA) concentration to induce complete fibrinolysis within 10 minutes was determined using serial dilutions of tPA in equine plasma. Results used to create an in vitro hyperfibrinolysis model with equine and human citrated plasma, and the minimum concentrations of EACA and TEA required to completely inhibit fibrinolysis for 30 minutes (estimated therapeutic concentrations) determined using serial dilutions of the drugs. Results Estimated therapeutic concentrations of EACA and TEA were significantly lower in horses (5.82; 95% CI 3.77–7.86 μg/mL and 0.512; 95% CI 0.277–0.748 μg/mL) than in humans (113.2; 95% CI 95.8–130.6 μg/mL and 11.4; 95% CI 8.62–14.1 μg/mL). Conclusions and Clinical Importance Current dosing schemes for EACA and TEA in horses may be as much as 20×  higher than necessary, potentially increasing cost of treatment and risk of adverse effects.